Numerical assessment of the minimum distance between holes in 3D components and evaluation of the use of twist drills in the hole-drilling method - Wilvert, Thiago (2018)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Mecânica, Florianópolis, 2018.